Unwrapping reworked crust at the Columbia supercontinent margin within central southern Amazon Craton using multi-source geophysics and geochronology data synergy - João G. Motta (Geoscience Frontiers, 2022)
The geometry and evolution of pre-existing basement in accretionary belts bordering supercontinents are often unclear. Integrative interpretation of long-wavelength potential field satellite data can image deep crust structure, improving our understanding of lithospheric processes that formed these margins bottom-up. Here, we present a multidisciplinary interpretation of the lithospheric architecture of the central southern Amazon Craton, a fragment of an accretionary belt at the southwestern Columbia supercontinent margin. Satellite-borne gravity and magnetic data, airborne magnetic data, passive seismic (Vp/Vs ratio, crustal thickness) and seismic tomography data reveals that basement terranes from the interior of the craton extend into the accretionary margin of Columbia. We demonstrate a vertically heterogeneous structure with an underlying strongly reworked pre-Columbia tectonic wedge that sustained prolonged modification during the supercontinent assembly as corroborated by Nd isotope and geochronology data. Nd isotope data suggest that the protracted orogenic wedge was influenced by subduction angle shifts over time, including addition of substantial juvenile material during slab retreat events. This interplay promoted Craton growth at the supercontinent margin while keeping a subtle record of the pre-existing framework. Our findings point to the possible misrepresentation of basement extension and geometry of supercontinent margins elsewhere.